2020
DOI: 10.1111/vop.12774
|View full text |Cite
|
Sign up to set email alerts
|

In vitro susceptibility of Aspergillus and Fusarium associated with equine keratitis to new antifungal drugs

Abstract: Objective To determine minimum inhibitory concentrations (MICs) of four fungal species isolated from horses presented with equine fungal keratitis (EFK) in the southeastern United States to previously untested azole, echinocandin, and carboxamide antifungal drugs. Methods In vitro assays were performed to determine the susceptibility of Aspergillus flavus, A. fumigatus, Fusarium falciforme, and F. keratoplasticum to five antifungal drugs representing three modes of action. Results Luliconazole exhibited increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Caspofungin penetrates through the cornea with a compromised epithelium (but not intact), resulting in aqueous humor drug levels above MICs for most fungi (21). Caspofungin has variable but sometimes good efficacy against Scopulariopsis sp., variable but sometimes good efficacy against Fusarium sp., shows no signs of corneal toxicity or irritation, and is intermediate cost to the client (7,8,15,21,25). No adverse reactions to any topical medications were noted in this case.…”
Section: Discussionmentioning
confidence: 67%
“…Caspofungin penetrates through the cornea with a compromised epithelium (but not intact), resulting in aqueous humor drug levels above MICs for most fungi (21). Caspofungin has variable but sometimes good efficacy against Scopulariopsis sp., variable but sometimes good efficacy against Fusarium sp., shows no signs of corneal toxicity or irritation, and is intermediate cost to the client (7,8,15,21,25). No adverse reactions to any topical medications were noted in this case.…”
Section: Discussionmentioning
confidence: 67%
“…Voriconazole can penetrate intact corneal epithelium which provides a major advantage in treatment of equine fungal keratitis and fungal abscesses 31 . A recent study investigated MICs of two Aspergillus species and two Fusarium species to voriconazole, pydiflumetofen, prothioconazole, caspofungin, and a novel azole, luliconazole 35 . They found that luliconazole had an increased growth inhibition and a 25‐fold lower MICs compared with other antifungals for both organisms 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated MICs of two Aspergillus species and two Fusarium species to voriconazole, pydiflumetofen, prothioconazole, caspofungin, and a novel azole, luliconazole 35 . They found that luliconazole had an increased growth inhibition and a 25‐fold lower MICs compared with other antifungals for both organisms 35 . Further clinical investigations of this novel azole in the clinical setting is required 35 …”
Section: Discussionmentioning
confidence: 99%
“…Several fungal genera are associated with keratomycosis, including Aspergillus, Fusarium, Candida, Curvularia, Penicillium, Cylindrocarpon, and Mucor (Galán et al 2009;Utter et al 2010;Galera & Brooks 2012;Wada et al 2013;Samanta 2015;Sherman et al 2017;Ledbetter et al 2018), the first two being the most frequently reported and with the worst prognosis (Galán et al 2009;Utter et al 2010;Cafarchia et al 2013;Sherman et al 2017;Roberts et al 2020). Since these genera are also found in healthy eyes (Khosravi et al 2014), a fungal culture must be conducted with histopathology and/or cytology to verify whether the tissue has been compromised with hyphae or yeast.…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal resistance is a concerning threat to fighting mycotic diseases such as the one discussed here. New drugs such as luliconazole (an imidazole used to treat keratomycosis in humans) have become a potential treatment for this disease caused by resistant Aspergillus or Fusarium species in horses, by exhibiting the lowest MICs (Minimum Inhibitory Concentrations) in antifungal susceptibility tests (Roberts et al 2020). However, its availability and price are restrictive to developing nations, highlighting the importance of implementing the proper treatment in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%